2020
DOI: 10.3390/molecules25092028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angelica gigas Nakai Ethanol Extract and Decursin on Human Pancreatic Cancer Cells

Abstract: Pancreatic cancer (PC) is one of the most severe cancers, and its incidence and mortality rates have steadily increased in the past decade. In this study, we demonstrate the effect of Angelica gigas Nakai extract on pancreatic ductal adenocarcinoma cells. We prepared A. gigas Nakai ethanol extract (AGE) using roots of A. gigas Nakai and detected its active compound decursin from AGE by ultra-performance liquid chromatography analysis. AGE and decursin significantly decreased viability and colony formation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Here, we evaluated the efficacy and associated mechanism of decursin for its anticancer activity against PCa cells. Decursin, a coumarin compound, was first isolated from the roots of Angelica gigas Nakai and has shown anticancer activity in various cancer types including PCa 17–21 . In our previous study, decursin was found to induce a G1 phase cell cycle arrest and apoptosis in PCa cells by modulating the levels of cyclin‐dependent kinases (CDKs), cyclins and CDK inhibitors 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we evaluated the efficacy and associated mechanism of decursin for its anticancer activity against PCa cells. Decursin, a coumarin compound, was first isolated from the roots of Angelica gigas Nakai and has shown anticancer activity in various cancer types including PCa 17–21 . In our previous study, decursin was found to induce a G1 phase cell cycle arrest and apoptosis in PCa cells by modulating the levels of cyclin‐dependent kinases (CDKs), cyclins and CDK inhibitors 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Decursin also mediates apoptosis through the phosphorylation of JNK and p38 and the downregulation of Bcl-2, CDK4, and cyclin D1 in glioblastoma cells U87 [ 14 ]. The ethanol extract of Angelica gigas inhibits cell viability and colony formation and induces apoptosis and G0/G1 arrest via the inhibition of cyclin D1, CDK4, MMP-2, MMP-9, and p38 phosphorylation in the pancreatic cancer cells PANC-1 and PaCa-2 [ 15 ]. Traditional Chinese medicine DangguiBuxue Tang (DBT) exerts anti-cancer effects in colorectal cancer cells, and a combination of DBT and radiation has more powerful anticancer effects compared to radiation or DBT alone [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…JI017 is a combination of herbal extracts from Angelica gigas (Ag), Zingiber officinale Roscoe (Zo), and Aconitum carmichaeli (Ac) in the ratio of 2:1:1. The anti-cancer effects of Ag, Zo, and Ac individually have been well reported in many cancer cells, including pancreatic cancer, liver cancer, breast cancer, lung cancer, and oral cancer [9][10][11][12]. Ag ethanol extracts induce caspase-3-dependent apoptosis by inhibiting MMP-2 and MMP-9 in Human pancreatic cancer cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-cancer effects of Ag, Zo, and Ac individually have been well reported in many cancer cells, including pancreatic cancer, liver cancer, breast cancer, lung cancer, and oral cancer [9][10][11][12]. Ag ethanol extracts induce caspase-3-dependent apoptosis by inhibiting MMP-2 and MMP-9 in Human pancreatic cancer cells [9]. Zo ethanol extracts mediate caspase-3-dependent apoptosis by activating autophagic cell death and cell cycle arrest [13].…”
Section: Introductionmentioning
confidence: 99%